Pengembangan Agrowisata Kopi di Lampung Barat - Adam Hafidz Al Fajar; El Fira Zidna Almaghfiro; Evi Fitri Aglina; Wafik Azisa; Wahyu Trisno Aji (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research explores the potential for developing coffee agro-tourism in West Lampung as a strategy to enhance the local economy while supporting sustainability. Although West Lampung is known as one of the top coffee producers in Indonesia, the development of agro-tourism in this region still faces various challenges, such as limited infrastructure, lack of promotion, and minimal community participation. By using a Systematic Literature Review (SLR) approach, this study aims to identify key factors influencing the success of coffee agro-tourism and provide recommendations to address these challenges. The study indicates that the development of coffee agro-tourism has the potential to improve the economic well-being of the community by increasing income, creating jobs, and preserving culture and the environment. Therefore, policies that support the strengthening of human resources, infrastructure development, effective promotion, and community involvement in the development of agro-tourism in West Lampung are needed. The results of this research are expected to serve as a reference for the government, local communities, and investors in designing more effective policies and programs for sustainable coffee agro-tourism development in this region.